Implementing Business Model In Hospital: A Scoping Review - Lastri Swastanita; Amal Chalik Sjaaf (Syntax Corporation, 2022)
Increased competition between hospitals, population growth, advances in medical technology, increased life expectancy, and digital transformation urges hospitals to adapt. Health care providers are stuck in situations that require cutting health costs while still maintaining the quality of care to patients. Many believe that the business model will be a major contributor to the sustainability of competitive advantage for hospitals. This research aimed to look at the role and application of hospital business models that can maintain quality, effective financing services, and sustainability. Searches for articles were conducted on four databases using PRISMA-ScR protocol. We included studies containing the business models in a hospital setting, using relevant search terms related to the hospital business model. Systematic search yielded five articles that lay out some of the business models. Sixty percent of articles were published in Asian countries. Study designs were descriptive and observational studies. Each business model has its uniqueness that can give an idea of how to run a business model tailored to the characteristics of the hospital itself.